Metafora drogi jako sposób intymizacji przeżycia duchowego. Na przykładzie wybranych medytacji z XVII i XVIII wieku - Łukarska, Beata (Colloquia Litteraria, 2023)
This text refers to the metaphor of the road as an image of human life. In the context of the considerations, the above-mentioned topos gains its extension and completion in detailed visions of wandering or pilgrimage to the heavenly homeland understood as the eschatological dimension of the final destiny of the soul of every human being. The first part of the study contains examples of the presence of the above-mentioned images in selected records of the biblical tradition and the tradition of Christian writing. In the further parts of the study, the basis of the analysis are selected manuscripts of monastic meditations, which are part of the rich collection of manuscripts of the Library of Ossoliński in Wrocław. These texts were written in the seventeenth and eighteenth centuries. They represent different artistic value. Their authors come from various religious traditions, including the Carmelite tradition and the 17th-century community of the Visitation Sisters.